The Titanic sunk, so what? Project manager response to unexpected events - Geraldi, Joana; Lee-Kelley, Liz; Kutsch, Elmar (Elsevier Science B.V., Amsterdam., 2010)
Projects are inherently uncertain and face unexpected events, from small changes in scope to unforeseen client's bankruptcy. This paper studies how project managers respond to such events and how successful and unsuccessful responses differ from the perspective of the practitioner. We analysed 44 unexpected events faced by 22 experienced project managers in defence and defence-related organisations. The project managers compared two unexpected events that they faced, one that they considered the response successful and the other unsuccessful. We identified three pillars supporting successful responses to unexpected events: (1) responsive and functioning structure at the organisational level, (2) good interpersonal relationship at the group level and (3) competent people at the individual level. The events and respective responses analysed suggest that improvement in project management can be achieved by better managing these three pillars, allowing project and programme managers to "create their own luck". (C) 2009 Elsevier Ltd and IPMA. All rights reserved.
Keywords: Unexpected events Perceived success Organisational response Project management flexibility uncertainty decision crisis risk